EFFECTS OF MAIZE BRAN DIETS ON THE GROWTH AND NUTRIENT UTILIZATION OF TILAPIA (Oreochromis niloticus) - FALAYE, A. E; OMOIKE, A. (Nigerian Journal of Fisheries, 2012)
Tilapia (Oreochromis niloticus Trewavas) fingerlings were fed 30 % crude protein isonitrogenous diets with maize bran replacing different proportion 0, 33. 3, 66.7 and 100% of the whole maize in the diet and were observed for growth response over time. Fish meal and groundnuts cake were the main dietary protein sources and mineral/ vitamin premix was added and the pelletized experimental diets stored in air-tight polythene bags. The fingerlings were fed for 49 days. Acclimatized tilapia fingerlings, with mean weight of 8.19 g, were stocked in four aerated glass aquaria tank measuring 47 x 28 x 32 cm at the rate of 15 per aquarium. Each experimental diet was assigned to a tank and fed to the fish twice daily and adjusted weekly later. Findings indicated increasing maize bran intake resulted in better weight gains and higher specific growth rates of 0.22, 0.25 and 0.25 per day respectively. The increase in growth from the feeding diets containing 66.7% and 100% of the maize replaced with maize bran were significantly higher (P < 0.05) than those of other diets. Fish fed with diets where whole maize was replaced 100% by maize bran, gave the best overall performance in terms of weight gain, food conversion efficiency and specific growth. The replacement of maize with maize bran is economical with no side effects as tilapia feeds.